2011
DOI: 10.1227/neu.0b013e31823110f1
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation Using the Middle Fossa Approach for the Treatment of Vestibular Schwannoma

Abstract: Hearing preservation rates are excellent using the middle fossa approach, especially for smaller tumors. No patient experienced long-term facial nerve function worse than House-Brackmann grade III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Although removal of medium or large ANs carries a considerable risk for facial palsy, 38 a series of recent studies of removal of small ANs reported high rates of facial function preservation (88%-100%) 9,13,16,18,21,23,24,27,36,37,42 (Table 3). In our study, the rate of normal facial function preservation (House-Brackmann Grade I) was 100%.…”
Section: Long-term Outcome Of Curative Small An Removal With Preservamentioning
confidence: 99%
“…Although removal of medium or large ANs carries a considerable risk for facial palsy, 38 a series of recent studies of removal of small ANs reported high rates of facial function preservation (88%-100%) 9,13,16,18,21,23,24,27,36,37,42 (Table 3). In our study, the rate of normal facial function preservation (House-Brackmann Grade I) was 100%.…”
Section: Long-term Outcome Of Curative Small An Removal With Preservamentioning
confidence: 99%
“…Prerequisites for the translabyrinthine approach include mainly the preoperative lack of serviceable hearing and the presence of larger tumors [9, 10]. The retrosigmoid (suboccipital) approach allows the removal of tumors of any size with the potential for hearing preservation; its main disadvantage is the need for cerebellar retraction [11, 12]. Lastly, the middle fossa approach is chosen for tumors limited to the internal auditory canal or with minimal CPA extension with an attempt to preserve hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Our long-term facial nerve function is comparable with previous studies. 12,13,19 Of 49 subjects, Woodson et al 19 reported that 46 (96%) exhibited HB grade 1 and 3 subjects exhibited HB grade 2 with more than 2 years of follow-up. Of the 33 patients with a 5-year follow-up, 4 (12%) exhibited tumor recurrence on MRI, which is consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%